Karl Barth and the Fifth Gospel: Barth’s Theological Exegesis of Isaiah. By Mark S. Gignilliat - Moberly, Walter (The journal of theological studies, 2010)
This book clearly and straightforwardly does what it sets out to do. Gignilliat offers an account of Karl Barth’s interpretation of the book of Isaiah. He thereby usefully fills a gap in existing secondary literature on Barth. Barth’s work on the Old Testament has generally received less attention than his work on the New Testament, not least because he did not write commentaries on Old Testament books as he did on certain New Testament books. Moreover, when attention has been given to Barth on the Old Testament, there has been a tendency to focus mainly on certain discrete discussions in the Church Dogmatics, such as those on creation or on election.